2002
DOI: 10.1046/j.1529-8817.2002.t01-1-01223.x
|View full text |Cite
|
Sign up to set email alerts
|

DETERMINATION OF CELLULAR LEVELS OF NONPROTEIN THIOLS IN PHYTOPLANKTON AND THEIR CORRELATIONS WITH SUSCEPTIBILITY TO MERCURY1

Abstract: We determined the intracellular contents and concentrations of cysteine and glutathione in five species of marine phytoplankton, Tetraselmis tetrathele (West) Butcher (Prasinophyceae), Porphyridium purpureum (Bory) Drew et Ross (Rhodophyceae), Pavlova sp. (Haptophyceae), Isochrysis sp. (Haptophyceae), and Pleurochrysis carterae (Braarud et Fagerl) Christensen (Haptophyceae), and examined relationships to mercury susceptibility. Intracellular contents (concentrations) of nonprotein thiols in the five species ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…Concentrations were 26 Ϯ 2.6 and 17 Ϯ 0.7 amol/cell (0.18 Ϯ 0.02 and 0.12 Ϯ 0.01 mM) for 6 and 24 h, respectively ( Table 2). In comparison, Satoh et al [6] observed that GSSG levels in unstressed marine algae were similar among species (0.15-0.26 mM). The GSH levels also were influenced significantly by incubation time ( p Ͻ 0.05) and decreased in Cu added flasks from 6 to 24 h. Apparently, GSH was depleted faster in the detoxification process than the rate of synthesis, Cu inhibited the production of GSH, and/or the GSH pool was depleted by phytochelatin synthesis.…”
Section: Influence Of Exposure Time On Endpoints For Detecting Cu Stressmentioning
confidence: 89%
See 1 more Smart Citation
“…Concentrations were 26 Ϯ 2.6 and 17 Ϯ 0.7 amol/cell (0.18 Ϯ 0.02 and 0.12 Ϯ 0.01 mM) for 6 and 24 h, respectively ( Table 2). In comparison, Satoh et al [6] observed that GSSG levels in unstressed marine algae were similar among species (0.15-0.26 mM). The GSH levels also were influenced significantly by incubation time ( p Ͻ 0.05) and decreased in Cu added flasks from 6 to 24 h. Apparently, GSH was depleted faster in the detoxification process than the rate of synthesis, Cu inhibited the production of GSH, and/or the GSH pool was depleted by phytochelatin synthesis.…”
Section: Influence Of Exposure Time On Endpoints For Detecting Cu Stressmentioning
confidence: 89%
“…Trace metal toxicity is the result of various effects, including disruption of enzymes, photoinhibition, substitution of essential metals, reactive oxygen species formation, and antioxidant depletion [1][2][3][4]. Glutathione (␥-glutamylcysteinylglycine) is the most abundant nonprotein thiol in all eukaryotic cells, typically present in millimolar concentrations (ranging from about 0.1-3.3 mM glutathione in nonstressed cells) [5,6], and functions as an antioxidant to protect cells from environmental stresses. It has been shown that depletion of this thiol results in oxidative stress as well [1].…”
Section: Introductionmentioning
confidence: 99%
“…This difference in the ability to induce the non-protein thiols among these strains might be due to variation in tolerance level to chromate. Although, there is very little information available about intracellular concentration of cysteine in living organisms, it is reported that in several species of eukaryotic algae, cysteine content ranges from 0.6 to 12 mM (Satoh et al , 2002). Cysteine concentrations of both P. aeruginosa Rb-1 and O. intermedium Rb-2 were also within this range.…”
Section: Discussionmentioning
confidence: 99%
“…Total GSH (Gamma-L-glutamyl-L-cysteninylglycine) and GSSG [Bis (gamma-Glutamyl-L-cysteinylglycine) Disulfide] were measured by the GSSG recycling method, with GSSG as the standard (Satoh et al , 2002). …”
Section: Methodsmentioning
confidence: 99%
“…For example, glutathione in marine phytoplankton ranges from 0.08 to 3.1 mM (Rijstenbil and Wijnholds, 1996) for phytoplankton, and 45.7 ± 0.92 mg/g protein for marine Decapoda (Wang et al, 2008). Cysteine in phytoplankton ranges from 0.04 to 2.23 mM, (Rijstenbil and Wijnholds, 1996;Satoh et al, 2002), and ascorbic acid ranges from 59 to 5400 μg/g dry weight (Brown and Miller, 1992;Maldonado, 2009). In our experiments we selected concentrations within these ranges.…”
Section: Int Reduction In Cell-free Homogenatesmentioning
confidence: 98%